Transforming fabrics into UV-sensing wearables: A photochromic hackmanite coating for repeatable detection - Lawrynowicz, Alicja; Vuori, Sami; Palo, Emilia; Winther, Mathias; Lastusaari, Mika; Miettunen, Kati (Elsevier BV, 2025)
In this study, we successfully present the first application of a hackmanite coating on a textile substrate to serve as a UV sensor. Photochromic minerals, such as hackmanite, are excellent candidates for designing accurate and long-lasting UV-sensing wearables capable of passively operating without external power sources. By incorporating hackmanites into textiles, UV monitoring can become more accessible and widespread, for example, preventing individuals from sunburn. Here, the resultant photochromic fabric revealed its capacity for swift color changes upon exposure to UV-A and UV-B irradiation, transitioning from white to purple within just 15 s. Subsequent exposure to white light led to a fast, complete reversal of coloration in approximately 50 min. The coloration of the fabric was assessed with reflectance spectroscopy, and the key information (i.e., UV index values) could be read with a proprietary phone app, Sensoglow. This app is designed to provide a convenient analysis of color change with the accuracy of integers values. Additionally, the hackmanite-coated fabric presented exceptional fatigue resistance, retaining consistent coloration across a minimum of 20 photochromic cycles. In contrast, alternative photochromic materials, such as tungstate-or spiropyran-based dyes, showed a gradual decrease in color saturation after just 10 cycles. Moreover, the hackmanite-coated fabric was proficient in monitoring UV index (UVI) values, even at levels below 3, a threshold for taking preventive measures, demonstrating that this fabric serves as a powerful tool for UV-sensing.